2007
DOI: 10.2320/matertrans.e-mra2007807
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Half-Heusler Type LaPdBi and GdPdBi

Abstract: The authors studied the thermoelectric properties of LaPdBi and GdPdBi half-Heusler compounds. Polycrystalline samples were prepared by a spark plasma sintering (SPS) technique, and their thermoelectric properties were measured above room temperature. The electrical resistivities of both samples show a semiconductor like behavior and are on the order of 10 À6 m. The estimated band gap energies of LaPdBi and GdPdBi are 0.05 and 0.07 eV, respectively. The values of the thermoelectric power are positive and decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
3
7
0
Order By: Relevance
“…Gofryk et al [100] reported that a non-trivial zero gap semiconducting state has been postulated for YPdBi with relatively small topological band inversion strength. TEP in LaPdBi and GdPdBi is positive and decreases with increasing temperature [594]. The differences in TEP and electrical resistivity between LaPdBi and GdPdBi arise due to the difference in band gap [594].…”
Section: Thermopower Thermal Expansion and Hall Measurementsmentioning
confidence: 93%
See 2 more Smart Citations
“…Gofryk et al [100] reported that a non-trivial zero gap semiconducting state has been postulated for YPdBi with relatively small topological band inversion strength. TEP in LaPdBi and GdPdBi is positive and decreases with increasing temperature [594]. The differences in TEP and electrical resistivity between LaPdBi and GdPdBi arise due to the difference in band gap [594].…”
Section: Thermopower Thermal Expansion and Hall Measurementsmentioning
confidence: 93%
“…The differences in TEP and electrical resistivity between LaPdBi and GdPdBi arise due to the difference in band gap [594]. The thermal conductivity of both the compounds increases with increase in temperature, signalling that the electronic thermal conductivity is predominant [594].…”
Section: Thermopower Thermal Expansion and Hall Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some issues involving relatively high thermal conductivity remain unsolved [2]. Recently, exploratory reports have shown that rare-earth (R) bearing half-Heusler phases RT X Sb can also exhibit good thermoelectric performance, characterized by fairly low thermal conductivity [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Based on these predictions, we examined in this work a series of Er1-xHoxNiSb samples with the main aim at determining the effect of rare-earth substitution on the magnitude of their thermoelectric power factor.…”
Section: Introductionmentioning
confidence: 99%
“…The first system is the heavy half-Heusler LaPtBi [7], which in most of the calculations exhibits a band-inversion [8] indicating that it represents a typical nontrivial semimetal. The lighter half-Heusler LaPdBi [9], which in calculations exhibits a small indirect band gap [1][2][3], will serve as a representative trivial system. Since both compounds have the same crystal structure, it might be possible to generate a series of isostructural La(Pt 1−x Pd x )Bi alloys, by continuously varying x from 0 to 1.…”
Section: Modelingmentioning
confidence: 99%